Towards local governance of marine resources and ecosystems on Easter Island. Issue 2 (14th May 2016) - Aburto, Jaime A.; Gaymer, Carlos F.; Cundill, Georgina
Abstract: Social‐ecological system sustainability depends in part upon the fit between ecosystems and institutions. In 2014, the local community on Easter Island started a bottom‐up process to improve marine resources conservation and management. Local stakeholders formed a working group that has regular meetings and goals, such as creating a sea council and some basic action plans, thus initiating a local governance transformation process. A participatory process was conducted together with a local organization that led the marine conservation issues on the island to define the factors that could favour and/or undermine the formation of the sea council. Also, the stakeholders that must be present in such a sea council were identified. Twelve factors that could facilitate or hinder the implementation of a sea council were identified. The lack of representativeness of public institutions is a major challenge. Public institutions are designed to ensure compliance with central government strategies, but the decisions do not represent the worldview of islanders. The results showed the potential value of conducting a participatory process to identify the key issues that could hinder or favour a desired governance transformation process. The participatory process also highlighted governance mismatches that are important to consider in attempts to pursue more effective fishery governance on Easter Island, and other Island communities. Centralized governance systems do not respond rapidly to locally observed social and ecological dynamics. By contrast, a local decision‐making system based on traditional laws and local governance can more rapidly respond to observed changes. The participatory process presented here holds the potential to support local people in their planning and coordination for marine conservation and management in order to optimize bottom‐up change processes involving multiple stakeholders with different interests, values and levels of power. Copyright © 2016 John Wiley & Sons, Ltd.